Endometrial neuroendocrine carcinoma and undifferentiated carcinoma are distinct entities with overlap in neuroendocrine marker expression. Issue 1 (5th May 2022) - Tessier‐Cloutier, Basile; Kang, Eun‐Young; Alex, Deepu; Stewart, Colin J R; McCluggage, W Glenn; Köbel, Martin; Lee, Cheng‐Han
Abstract : Aims: Dedifferentiated endometrial carcinomas (DDECs)/undifferentiated endometrial carcinomas (UDECs) frequently harbour genomic activation of switch/sucrose non‐fermentable (SWI/SNF)‐complex proteins, and can show histological overlap with neuroendocrine carcinoma (NEC). The aim of this study was to compare the extent of the expression of neuroendocrine markers, SWI/SNF proteins and mismatch repair (MMR) proteins in DDEC/UDEC and NEC. Methods and results: The extent of expression of synaptophysin, chromogranin, CD56, ARID1A, ARID1B, SMARCA4, SMARCB1 and MMR proteins was evaluated by immunohistochemistry on 44 SWI/SNF‐deficient DDECs/UDECs and 15 NECs. Thirty‐three of 44 (75%) DDECs/UDECs showed expression of at least one neuroendocrine marker, with 18 of 44 (41%) expressing two or more neuroendocrine markers, whereas all 15 NECs showed expression of at least one neuroendocrine marker, with 14 of 15 (93%) expressing two or more neuroendocrine markers. Neuroendocrine marker expression in DDECs/UDECs was typically focal when present, with average extents of 17%, 4% and 8% for synaptophysin, chromogranin and CD56 in the positive cases, respectively, in contrast to 73%, 40% and 62% in the positive NEC cases, respectively. All 15 NECs showed intact expression of SWI/SNF‐complex proteins, except for one that showed isolated loss of ARID1A. Thirty‐eight of 44 DDECs/UDECs were MMR‐abnormal (34 with loss of MLH1 and PMS2, and four with loss of PMS2 alone), whereas all NECs retained MMR protein expression. Conclusions: Our study demonstrates frequent but typically focal neuroendocrine marker expression in SWI/SNF‐deficient DDECs/UDECs, whereas NECs typically express two or more neuroendocrine markers, with diffuse expression of at least one marker. ARID1B, SMARCA4 and SMARCB1 immunohistochemistry can be used to aid in the differentiation between DDEC/UDEC and NEC. Abstract :